Comparative Corneal Histomorphometry Between Birds of Different Species - Rafaela A. R. Tozetti; Matheus V. L. Moreira; Rosélia L. S. Araújo; Liria Q. L. Hirano; Bret A. Moore; Paula D. Galera (Biology)
To describe the corneal histomorphometry of 8 birds from different species, this study analyzed 11 eyes from individuals that had recently died due to various causes. Only healthy eyes were included, representing the following species: Asio stygius, Crotophaga ani, Pitangus sulphuratus, Turdus rufiventris, Ramphastos toco, Rhea americana, Ara macao, and Nyctibius griseus. The eyes were enucleated within 30 min after death and fixed in 10% formaldehyde. The corneas were analyzed by light microscopy to measure and describe their layers. While the general structure and composition were consistent with those of other vertebrates, significant differences were found among species in the thickness of the corneal layers. These differences were observed between the central and peripheral regions of the same cornea, as well as between species. The central region was predominantly thinner than the periphery. Epithelial thickness varied from 2% to 16% of the total corneal thickness. The number of epithelial layers also varied between species, ranging from three to six. Bowman’s layer was present in all birds studied, and the stroma was the thickest layer in every sample. These findings contribute to a better understanding of the corneal morphology in diverse bird species and may support future ophthalmic or comparative anatomical research.